2021
DOI: 10.1016/j.jsxm.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Post-Finasteride Syndrome Patients

Abstract: Background An organic etiology underpinning post-finasteride syndrome, a constellation of persistent sexual, neuropsychiatric, and somatic symptoms reported by men exposed to 5-alpha-reductase inhibitors (5ARIs), is debated. Persistent changes in neurosteroid levels or androgen receptor expression have been implicated. Aim To determine whether differences in gene expression, especially in relevant biologic pathways, exist bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Research conducted on a cell line derived from Caucasian human prostate carcinoma (LNCap), in a model of androgen-dependent prostate cancer, revealed that the exposure of cells to Fin for 1–6 months increased AR expression [ 41 ]. A study reporting symptoms consistent with post-finasteride syndrome (PFS) was conducted on samples of penile skin from 26 men with a history of using 5-alpha-reductase inhibitors, and showed significantly higher AR expression compared to the controls [ 42 ]. It has also been demonstrated that AR and the gene expression of UPR are correlated in prostate cancer.…”
Section: Finasteride Testosterone and Androgen Receptormentioning
confidence: 99%
“…Research conducted on a cell line derived from Caucasian human prostate carcinoma (LNCap), in a model of androgen-dependent prostate cancer, revealed that the exposure of cells to Fin for 1–6 months increased AR expression [ 41 ]. A study reporting symptoms consistent with post-finasteride syndrome (PFS) was conducted on samples of penile skin from 26 men with a history of using 5-alpha-reductase inhibitors, and showed significantly higher AR expression compared to the controls [ 42 ]. It has also been demonstrated that AR and the gene expression of UPR are correlated in prostate cancer.…”
Section: Finasteride Testosterone and Androgen Receptormentioning
confidence: 99%
“…27 higher expression of AR in penile tissue of post-finasteride patients. 94 Androgen mediation of post-ischemic neoangiogenesis Androgens, AR and age also mediate the response to ischemic events. Lam et al…”
Section: Androgen Mediation Of Angiogenesismentioning
confidence: 99%
“…Human and animal studies have identified differences in neuroactive steroid levels, gut microbiota composition and gene expression persisting after discontinuation of finasteride. 33,80,94,116,117 The neuroendocrine system, microbiome and epigenome are intricate, sensitive domains which may reflect diet, environment, health conditions, medication exposures, sleep and stress. Therefore, even a robust finding of post-5ARI differences in these domains does not necessarily explain the pathogenesis of PD-5ARI.…”
Section: Neuroendocrine Microbiotic and Epigenetic Changes Associated...mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Interestingly, these side effects may persist after the drug suspension, inducing the so-called post-finasteride syndrome (PFS). 9,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The effects of finasteride treatment were also reported in animal models. For instance, finasteride treatment in castrated rats decreased erectile response, although receiving T replacement 35,36 and in control male rats, it decreased intracavernosal pressure during electrical stimulation of cavernous nerves.…”
Section: Introductionmentioning
confidence: 97%